Perencanaan karier siswa ditinjau dari konsep diri - Prika Dewi; Sri Utami; Anna Rufaidah (Orien: Cakrawala Ilmiah Mahasiswa, 2023)
this study aims to describe the effect of self-concept on students' career planning. This research is a quantitative research with a survey type. The sample in this study was drawn using the Slovin formula with an error degree of 0.05 from a total population of 230 students. Through this formulation a sample of 147 students was obtained. Data was collected through self-concept and career planning questionnaires. Data were analyzed using a simple linear regression test. This study concludes that self-concept has a significant effect on students' career planning.